INVESTIGATION OF THE PHOTOMETRIC SYSTEM OF CCD-PHOTOMETER AND THE AZT-3 TELESCOPE - Udovichenko, S. N. (Одеські астрономічні публікації, 2012)
The investigation of the photometric system consisting from photometer with CCD detector Sony ICX429ALL, VRI filters and the AZT-3 telescope was carried out. The transformation coefficients from the instrumental values of magnitudes and color indices to the Johnson-Cousins system in the VRI passbands are presented. The instrumental system of telescope and standard system have satisfactory agreement.